PENERAPAN DMAIC SIX SIGMA UNTUK PENGENDALIAN KUALITAS KERTAS ROKOK: STUDI KASUS PADA PAPER MACHINE 2 DI PT BUKIT MURIA JAYA - Veronica, Uzi Al; zizah, Fahriza Nurul A; Wahyudin, Wahyudin; Kharsima, Nadhira Septias (Institut Teknologi Dirgantara Adisutjipto, 2025)
PT Bukit Muria Jaya, a manufacturer of cigarette paper and packaging, encountered quality challenges with its Coresta 31-grade paper in January 2023, with defect rates surpassing the company's KPI threshold of 5%. This study innovatively adapted the DMAIC Six sigma methodology to the context of the cigarette paper industry, a sector characterized by unique production processes. By integrating tools such as Pareto and fishbone diagrams, the analysis identified stretch defects (49%) and smoothness defects (43%) as priorities, along with their root causes stemming from machinery, materials, and methods. Proposed improvements include adjustments to draw settings, refinement of grinding levels, and optimization of stretch and tensile properties. This approach not only provides specific solutions but also offers a sustainable improvement model applicable to similar industries